Nature Natured and Nature Denatured. (November 2014) - Bennett, Gaymon
Abstract Those who want to observe, analyze, and make judgments about synthetic biology need to think about where to stand in the world so as to get an informed sense of which new capacities and incapacities are actual and which matter. They will need something like "upstream ethics"—but not because they want to "get ahead" of the imagined onslaught of the technology. After all, the imagined capacities may remain entirely overstated. They will need upstream ethics because the question of which new capacities and incapacities are being brought into the world is unlikely to be found at the level of what bioengineers say about the work that they are doing. It is more likely to be found in the everyday spaces of practice in which engineers face the painstaking labor of making living beings that work. Those who want upstream ethics will also need to observe the relation between talk of synthetic biology and the extra‐technological effects such talk sets into motion—from the mobilization of capital to the activation of new power relations, anxieties, and displacements. It's in this motion that the biotechnical dreams generated by synthetic biology do their primary work. Any democratic deliberation about synthetic biology will need to operate as much on the ethical and political artifacts of these dreams as on any novel organisms synthetic biologists hope to build.